MSME INTERNATIONALIZATION EMPOWERMENT STRATEGY: FURNITURE CASE STUDY IN PASURUAN, EAST JAVA - Akhlis Priya Pambudy; Sudarmiatin; Imam Mukhlis (Jurnal Scientia, 2022)
In Indonesia's economic development, SMEs are the backbone of the people's economic system to reduce poverty problems, and their development can broaden the economic base and improve the economy. In order for Pasuruan Furniture SMEs to survive in exporting furniture production, an appropriate strategic model is needed to continue their existence in free trade flows. In research using qualitative methods, data collection methods interviews, participant observation and documentary research. Data analysis techniques for this study then used data acquisition, data reduction, data display, and inference from data analysis. The results of the study show that Furniture SMEs in Pasuruan can survive by using a production strategy that is characterized and serving orders based on customer wishes combined through innovation, product improvement and then applying social capital through expanding business networks